Mobile message communications for broadcast announcements and info: possible factors influencing acceptance by business users of alert services - Dix, Stephen; Unger, B.; Cole, A.; Kanabar, V. (The International Management Development Association (IMDA), 2012)
This paper explores acceptance of Short Messaging Service, (often referred to as SMS, text or mobile messages,) among business users of short burst alert services featuring announcements and timely information. Interviews were done with fourteen mobile phone subscribers in the United States who had signed up for alert services from a stock market publication, and either remained as subscribers or had unsubscribed within a three month period. Those who continued to subscribe said they were already active users of P2P (person to person) SMS, did not have cost issues, and especially emphasized the actionable value of content as key to their continued usage. Un-subscribers said that they did not find enough value from the content delivered, and in some cases also described themselves as concerned about perceived costs for receiving text messages, and as less frequent users of SMS, even P2P. Neither group stressed concerns about previous negative SMS experience, security, or spamming, but several individuals in both cohorts wanted more control of the experience, including its frequency and timing.